WORKING COMMUNITIES’ SIGNIFICANT HERITAGE URBAN RIVER CORRIDOR LANDSCAPE OF MELAKA CITY - Zainal Abidin, Nor Arbina; Debra Flanders, Cushing; Gillian, Lawson (PLANNING MALAYSIA, 2020)
The existing landscape characters of urban river corridor of Melaka City have eroded due to unsustainable design outcomes due to inadequate policies and guidelines, indiscriminate decision in design and it lacks of community consultation. In addition, political intervention and climate change have made it worse to the present urban river corridor of the city. These issues have raised concerns among the local community, particularly those workers whose livelihood depend on resources in that area. This paper reveals the distribution patterns and landscape settings of the urban river corridor of Melaka City which are significant among working communities. It also describes each landscape setting within the identified territory. The findings are determined via thematic coding analysis and overlay mapping technique based on the experiential landscape theory established by Thwaites and Simkins (2007). The combination of experiential landscapes from different individuals via overlay mapping analysis also provides insight into the communities’ urban river corridor boundary of the city, which is important in heritage-related policy